Pola Patronasi Amerika Serikat Studi Kasus: Plan Colombia Tahun 1999 – 2005 - Gowindha, Putu Ayu Laksmi (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRACT This research aims to describe the patronage pattern performed by the United States to Colombia in efforts to combat drug s trafficking . A s a form of transnational crime , d rugs trafficking has caused negative impact on the United States , it attacks the stability of the United States’ national security. On the other side, Colombia was seeking a way to reduce the chaos in the country which is caused by the drugs cartels. In 1999 the Government of Colombia created a development program named Plan Colombia to bring the peace back. Nevertheless, Colombia could not perform the program effectively without aids from other countries or the international community. The United States saw an opportunity to build an international cooperation through Plan Colombia based on some of the points that matched to the United States’ goal to combat drug s trafficking. The United States considered that by being the patron on Plan Colombia, the program could be optimally implemented. Keywords : Patron-Client, the United States, Colombia, Plan Colombia